Modelling Extraction of White Tea Polyphenols: The Influence of Temperature and Ethanol Concentration - Sara Peiró; Michael H. Gordon; Mónica Blanco; Francisca Pérez-Llamas; Francisco Segovia; María Pilar Almajano (MDPI AG, 2014)
The optimization of the extraction of natural antioxidants from white tea has fostered intensive research. This study has investigated the effects of ethanol-water mixtures, temperature and time on the extraction of polyphenols and antioxidant components from white tea. The response surface methodology was applied to identify the best extraction conditions. The best conditions to maximize the extraction of total polyphenols were: ethanol, 50%, for 47.5 min. Although the yield of polyphenols was optimal at 65 °C, the maximum antioxidant capacity was achieved with an extraction temperature of 90 °C. This study has identified the optimal conditions for the extraction of tea liquor with the best antioxidant properties. Epigallocatechin gallate, epicatechin gallate, epigallocatechin and epicatechin were extracted from white tea at concentrations up to 29.6 ± 10.6, 5.40 ± 2.09, 5.04 ± 0.20 and 2.48 ± 1.10 mg/100 g.